Influence of polluted seawater on oxidation behaviour of Aluminum Alloy - Mohammed Misbahul, Amin; Ting, Tai Poh Yee; Ku Halim, Ku Bulat (Research Journal of Chemistry and Environment, 2009)
Organized by Research Journal of Chemistry and Environment, 24th - 26th December 2005 at The Emerald Heights International School, Indore, India.